PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 29 BUKIT KERIKIL KECAMATAN BUKIT BATU - Ahmad Khairul Anam; Lazim N '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Background problem in this research is the low student learning outcomes IPA, with an average grade 62.50. Among students of 20 people only 9 students who completed reached KKM with classical completeness 45%. Given the importance of learning science, then one way to improve student achievement in elementary school is to select methods appropriate learning. One appropriate method is used is a method of inquiry. The subjects were fifth grade students of SDN 29 Gravel Hill Bukit Batu subdistrict Bengkalis. Academic Year 2015/2016, the number of students 20 people, consisting of eight men and 12 women. The research instrument used to collect data in this study is the syllabus, RPPdan LKS. The Data Analysis technique used is the analysis of activities of teachers and students and analysis of student learning outcomes. Based on the results of data analysis Improved after the adoption of Inquiry Learning model looks at the teacher activity cycle I and cycle II at the first meeting 55%, 60% the second meeting, the third meeting 80%, and the fourth meeting of 90%. While the activities of students in the first cycle and the second cycle at the first meeting 55%, 60% the second meeting, the third meeting of the fourth meeting of 75% and 85%. Learning outcomes of the first cycle and the second cycle, the basic score indicates that finished only 9 or 45% and who did not complete 11 or 55%. At UH I, which completed numbering 12 people or 60% were not completed 8 or 40%. At UH II that all students completed 20 or 100%. The average value of students also increased, the average base score 62.75 student scores increased in UH I to 67 with an increase of 19.64%. While at UH II also increased the average value of student learning outcomes to 79 with an increase of 41.07%. Key words: Model Inquiry Learning, Learning Outcomes IPA